Structure of a pre-catalytic spliceosome - Plaschka, Clemens; Lin, Pei-Chun; Nagai, Kiyoshi (Nature (London), 2017)
Intron removal requires assembly of the spliceosome on precursor mRNA (pre-mRNA) and extensive remodelling to form the spliceosome’s catalytic centre. Here we report the cryo-electron microscopy structure of the yeast Saccharomyces cerevisiae pre-catalytic B complex spliceosome at near-atomic resolution. The mobile U2 small nuclear ribonucleoprotein particle (snRNP) associates with U4/U6.U5 tri-snRNP through the U2/U6 helix II and an interface between U4/U6 di-snRNP and the U2 snRNP SF3b-containing domain, which also transiently contacts the helicase Brr2. The 3′ region of the U2 snRNP is flexibly attached to the SF3b-containing domain and protrudes over the concave surface of tri-snRNP, where the U1 snRNP may reside before its release from the pre-mRNA 5′ splice site. The U6 ACAGAGA sequence forms a hairpin that weakly tethers the 5′ splice site. The B complex proteins Prp38, Snu23 and Spp381 bind the Prp8 N-terminal domain and stabilize U6 ACAGAGA stem–pre-mRNA and Brr2–U4 small nuclear RNA interactions. These results provide important insights into the events leading to active site formation. The cryo-electron microscopy structure of the yeast spliceosome in a pre-catalytic state provides insights into the molecular events leading to formation of the spliceosome active site. Visualization of a poised spliceosome Protein-coding regions of DNA can be interrupted by non-coding regions, or introns. A large multisubunit complex, the spliceosome, is used to excise introns from the messenger RNA before it is translated into protein. Formation of an active spliceosome complex on an intron requires stepwise assembly of subcomplexes, followed by their rearrangement and the loss of some factors. Kiyoshi Nagai and colleagues have solved the structure of the B complex spliceosome, poised in a pre-catalytic state. The detection of several factors that were not visualized in previous spliceosome structures provides new insights regarding the process by which the complex is activated.